KEUNIKAN BANGUNAN BALE SAKENEM (WONG KILAS) DI BATUAN - I Gede Rikyana; I Nyoman Gde Suardana; I Ketut Adhimastra (Universitas Dwijendra, 2016)
Mr. I Wayan country house located in the village of Batuan Gianyar will be used as research material to Determine the uniqueness of the building Bale Dangin Sakenem, while the elements that will be Discussed, Among others, layout, shape of the building, use of materials , Structures . The method used is the method of collection of data, preparation of data and the data analysis, the resulting in a conclusion of the research objectives Keywords: The uniqueness of the building , Bale Sakenem ( wong kilas).